The Canadian Bronchiectasis and Nontuberculous Mycobacteria Registry: a study protocol - Christina S. Thornton; Nicole Boechler; Vidhi Desai; Ranjani Somayaji; Swathi Purighalla; Sarah Brode; Theodore K. Marras; Ryan Cooper; Maeve Smith; Julie Jarand (ERJ Open Research)
Background Bronchiectasis is a complex, chronic disease with geographic and ethnic diversity. While the most substantial cohort studies have been conducted in Europe and the USA, Canada also faces considerable challenges. The comprehensive Canadian Bronchiectasis and Nontuberculous Mycobacterial (NTM) Registry aims to 1) outline the clinical characteristics and natural history of bronchiectasis in Canada, 2) identify risk factors contributing to disease progression within Canadians, 3) integrate comprehensive clinical information to better understand the phenotypes of bronchiectasis and 4) support the development of large-scale, randomised controlled trials in Canada. Methods The Canadian Bronchiectasis and NTM Registry is an ongoing prospective, longitudinal, multi-centre, observational cohort study. It aims to enrol at least 2000 participants to collect data such as medical history, aetiological assessments, lung function tests, microbiological profiles, radiographic evaluations, comorbidities and quality of life (QoL) metrics. Participants will undergo annual follow-ups to gather longitudinal information regarding outcomes, treatments and changes in QoL. The inclusion criteria are a diagnosis of bronchiectasis by clinical history and computed tomography and/or pulmonary NTM infection as defined by American Thoracic Society/Infectious Diseases Society of America guidelines. The study's protocol received ethical approval from the lead site, the University of Calgary, with future additional approval from local ethics committees at all participating centres. Discussion The outcomes of the registry will be instrumental in uncovering the clinical traits and natural history of bronchiectasis. This longitudinal study will be used for analysis to form evidence-based clinical practices and serve as a resource in Canada to inform future studies in NTM and bronchiectasis.